Parodie, trawestacje, uwertury – znaczenie zabiegów stylizacyjnych w szkolnych etiudach Marka Piwowskiego - Mąka-Malatytńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The subject of the article Parodies, travesties, overtures – meaning of styling treatments in Mark Piwowski’s school films are Marek Piwowski’s early, short films and the stylistic and parodic elements he used. As the starting point of the discussion, Katarzyna Maka-Malatynska adopts the findings of Jerzy Ziomek and Ryszard Nycz, and their definition of parody. Using categories of literary and film studies, the author examines four school films of the creator of The Cruise. Acknowledging parody as the first degree of mockumentary after Roscoe and Hight, she proposes that Piwowski’s first films be seen as mockumentary, which could result in a new interpretation of his later works.